Israel`s Palestinians the conflict within - Peleg, Ilan 1944-; Waxman, Dov (Cambridge Cambridge University Press, 2011)
"This timely book explores the causes and consequences of the growing conflict between Israel's Jewish majority and its Palestinian-Arab minority"--
"Arguing that a comprehensive and lasting solution to the Israeli-Palestinian conflict depends on a resolution of the Jewish-Palestinian conflict within Israel as much as it does on resolving the conflict between Israel and Palestinians in the Occupied Territories, this timely book explores the causes and consequences of the growing conflict between Israel's Jewish majority and its Palestinian-Arab minority. It warns that if Jewish-Arab relations in Israel continue to deteriorate, this will pose a serious threat to the stability of Israel, to the quality of Israeli democracy, and to the potential for peace in the Middle East. The book examines the views and attitudes of both the Palestinian minority and the Jewish majority, as well as the Israeli state's historic approach to its Arab citizens. Drawing upon the experience of other states with national minorities, the authors put forward specific proposals for safeguarding and enhancing the rights of the Palestinian minority while maintaining the country's Jewish identity"--
Machine generated contents note: Introduction: the other Palestinian problem; Part I. The Conflict Within: 1. Palestinians in Israel: separate and unequal; 2. Palestinian politics in a Jewish state; 3. A radicalized minority?; 4. The Jewish majority and the Arab 'other'; Part II. Managing the Conflict: 5. The formation of the Jewish Republic; 6. Alternatives to ethnic hegemony; 7. Neither ethnocracy nor binationalism: seeking the middle ground; 8. Israel's challenge: moving from hegemony to equality; Conclusion: a comprehensive resolution of the Palestinian problem.
Includes bibliographical references and index.
Keywords: Palestinian Arabs; Jewish-Arab relations; Arab-Israeli conflict -- 1993-; POLITICAL SCIENCE / Government / International